Flexible all-solid-state battery manufacturing method

The method for manufacturing a flexible all-solid-state battery addresses inflexibility and space constraints by creating notches and crushing grooves, enabling folding and stacking for improved space utilization and functionality.

KR103042256B1Active Publication Date: 2026-11-05INNOSY M
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
KR1020240079416
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-06-19
Publication Date
2026-11-05
Estimated Expiration
2044-06-19

AI Technical Summary

Technical Problem

Conventional all-solid-state batteries using oxide-based solid electrolytes are inflexible and prone to damage or electrolyte leakage when folded or bent, and occupy significant installation space, limiting their utilization and space efficiency.

Method used

A method for manufacturing a flexible all-solid-state battery involves preparing a solid electrolyte sheet, forming a battery base body, bonding conductive films, and performing laser processing to create notches and crushing grooves, allowing the battery to be folded and stacked into specific length units.

Benefits of technology

The battery becomes flexible, enabling it to be folded or bent and stacked, thus serving as a parallel microbattery, reducing space requirements and enhancing installation flexibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure R1020240079416_ABST
    Figure R1020240079416_ABST
Patent Text Reader

Abstract

The present invention provides a method for manufacturing a flexible all-solid-state battery having a solid electrolyte, comprising the steps of: a) preparing a solid electrolyte sheet; b) preparing a battery base body using the prepared solid electrolyte sheet; c) firing the prepared battery base body; d) bonding a conductive film to one side and the other side of the battery base body after firing is completed; e) crushing the battery base body; and f) folding and stacking the battery base body with the conductive film bonded to its surface, so that the all-solid-state battery having the solid electrolyte is manufactured to be flexible, allowing the all-solid-state battery to be folded or bent into corresponding length units, and the solid electrolyte sheet is folded or bent into corresponding length units and stacked into corresponding length units, thereby enabling it to be utilized as a parallel micro battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a method for manufacturing an all-solid-state battery, and more specifically, to a method for manufacturing a flexible all-solid-state battery in which an all-solid-state battery having a solid electrolyte is manufactured to be flexible, and the all-solid-state battery can be folded into a corresponding length unit and then stacked in the folded length unit. Background Technology

[0003] Advancements in science and technology have driven the rapid development of lithium-ion rechargeable batteries that supply electrical energy to everyday electronic products, but lithium-ion rechargeable batteries pose potential safety risks during use, such as electrolyte leakage, combustion, and explosion.

[0004] Since batteries must be safe before they can meet the demands of normal human production and life, the safety of lithium-ion secondary batteries is also becoming an issue that researchers are exploring.

[0005] Currently, the main solution to solving lithium-ion secondary battery electrolyte leakage is to use solid electrolytes, which have advantages incomparable to liquid electrolytes and can be a technical path to solving the safety issues of lithium-ion secondary batteries.

[0006] In addition, all-solid-state lithium-ion secondary batteries have significant advantages over liquid-state lithium-ion secondary batteries, such as widening the operating temperature range, improving the energy density of the battery, and extending the service life.

[0007] All-solid electrolytes are oxide-based solid electrolytes, classified into inorganic solid electrolytes (ISE), solid polymer electrolytes (SPE), and composite polymer electrolytes (CPE). Inorganic solid electrolytes (ISE) are composed of inorganic materials in a crystalline or glassy state, and depending on the crystal structure, there are LISICON (LGPS, LiSiPS, LiPS), NALISICON (LTP, LATP, LAGP), pseudo-Argyrodite, garnet (LLZO), lithium nitrides, lithium hydrides, perovskites, lithium halides, lithium phosphorus oxynitrides, lithium thiophosphorus phosphate, and solid electrolytes having a solid form (having strength and brittleness).

[0008] In the case of the aforementioned inorganic solid electrolyte (oxide-based), if it is destroyed by external impact after firing, it cannot function as a battery, and furthermore, its shape cannot be changed after firing (it breaks like ceramics).

[0009] Therefore, all-solid-state batteries using oxide-based solid electrolytes could not be folded or bent due to the characteristics of the solid electrolyte, and if conventional all-solid-state batteries were forcibly folded or bent, there was a problem in that the battery would be damaged or a portion of the solid electrolyte inside the battery would leak out.

[0010] In addition, when installing all-solid-state batteries in devices, there was a problem in that they occupied a large amount of installation space, which imposed limitations on space utilization.

[0011] For prior art, refer to Registered Patent No. 10-2515623 (March 24, 2023). The problem to be solved

[0013] The present invention aims to provide a method for manufacturing a flexible all-solid-state battery having a solid electrolyte, wherein the all-solid-state battery is manufactured to be flexible so that it can be folded or bent in units of length, and the solid electrolyte sheets are folded or bent in units of length and stacked in units of length, thereby enabling it to be utilized as a parallel microbattery. means of solving the problem

[0015] A method for manufacturing a flexible all-solid-state battery according to the present invention comprises: a) a step of preparing a solid electrolyte sheet; b) a step of preparing a battery base body using the prepared solid electrolyte sheet; c) a step of calcining the prepared battery base body; d) a step of bonding a conductive film to one side and the other side of the battery base body after calcination is completed; and e) a step of crushing the battery base body. f) a step of bending a battery base body with a conductive film bonded to its surface, and the step of firing the prepared battery base body, which is step c), further includes a process of forming a notch of a certain depth on the surface of the battery base body that has been fired by laser processing when the firing of the battery base body is completed, and the step of crushing the battery base body, which is step e), is carried out together with the step of bonding a conductive film to one side and the other side of the battery base body that has been fired, which is step d), wherein a pressure roller that bonds a conductive film to one side and the other side of the battery base body presses the notch formed on the surface of the battery base body, thereby forming a crack with a length in the longitudinal direction of the notch formed on the surface of the battery base body and crushing it.

[0016] At this time, the battery base body according to the present invention may have a positive electrode layer laminated on one side of the solid electrolyte sheet and a negative electrode layer laminated on the other side of the solid electrolyte sheet, and a current collector layer further laminated on each of the positive electrode layer and the negative electrode layer.

[0017] And when a battery base body is prepared by laminating an anode layer, a cathode layer, and a current collector layer on the solid electrolyte sheet according to the present invention, a crushing groove of a certain depth can be formed on the surface of the battery base body using a cutting blade.

[0018] At this time, it is preferable that the longitudinal direction of the crushing groove according to the present invention is formed parallel to the bending axis of the all-solid-state battery.

[0019] delete

[0020] At this time, it is preferable that the longitudinal direction of the notch according to the present invention be formed parallel to the bending axis of the all-solid-state battery.

[0021] In addition, when the battery base body according to the present invention is bent, it is preferable that the battery base body be bent with an axis in a direction perpendicular to the longitudinal direction of the battery base body. Effects of the invention

[0023] The effects produced by the method for manufacturing a flexible all-solid-state battery according to the present invention are as follows.

[0024] An all-solid-state battery having a solid electrolyte is manufactured to be flexible, allowing it to be folded or bent to a specific length. As the solid electrolyte sheets are folded or bent to a specific length and stacked, they can be utilized as a parallel microbattery. Brief explanation of the drawing

[0026] FIG. 1 is an exemplary diagram briefly showing the process of manufacturing an all-solid-state battery by a method for manufacturing a flexible all-solid-state battery according to the first embodiment of the present invention. FIG. 2 is an exemplary diagram showing the state in which an all-solid-state battery is folded and stacked by a method for manufacturing a flexible all-solid-state battery according to the first embodiment of the present invention. FIG. 3 is an exemplary diagram briefly showing the process of manufacturing an all-solid-state battery by a flexible all-solid-state battery manufacturing method according to a second embodiment of the present invention. Specific details for implementing the invention

[0027] Hereinafter, preferred embodiments according to the present invention will be described in detail with reference to the attached drawings. Prior to this, terms and words used in this specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, and should be interpreted in a meaning and concept consistent with the technical spirit of the present invention, based on the principle that the inventor can appropriately define the concept of the terms to best describe his invention.

[0028] Therefore, the embodiments described in this specification and the configurations illustrated in the drawings are merely the most preferred embodiments of the present invention and do not represent all of the technical ideas of the present invention; thus, it should be understood that there may be equivalent variations that can replace them at the time of filing this application.

[0029] The present invention relates to a method for manufacturing a flexible all-solid-state battery having a solid electrolyte, wherein the all-solid-state battery is manufactured to be flexible, can be folded into corresponding length units, and can be stacked into folded length units. Referring to the drawings, the method is as follows.

[0030] A method for manufacturing a flexible all-solid-state battery according to an embodiment of the present invention with reference to FIGS. 1 to 3 comprises: a) a step of preparing a solid electrolyte sheet; b) a step of preparing a battery base body using the prepared solid electrolyte sheet; c) a step of firing the prepared battery base body; d) a step of bonding a conductive film to one side and the other side of the battery base body after firing is completed; e) a step of crushing the battery base body; and f) a step of folding and stacking the battery base body with the conductive film bonded to its surface.

[0031] The method for manufacturing a flexible all-solid-state battery of the present invention described above is divided into [Example 1] with a current collector + positive electrode + solid electrolyte + negative electrode + current collector structure and [Example 2] with a positive electrode + solid electrolyte + negative electrode structure, and each example is examined in more detail step by step as follows.

[0032] Referring to FIGS. 1 and FIGS. 2, first, in step a), a solid electrolyte sheet (10) is prepared.

[0033] At this time, the solid electrolyte sheet (10) is prepared by preparing an electrolyte raw material (oxide-based solid electrolyte) as a fine powder, mixing a binder and a solvent with the corresponding properties with the fine powder to form a slurry, and then processing the slurry through one of the casting processes of tape casting, slot die casting, and doctor braid casting to form a solid electrolyte sheet (10) with a thickness of several µm to several hundred µm.

[0034] Here, the slurry containing the electrolyte raw material is dried during casting, and as the moisture (solvent) contained in the slurry is removed, it hardens into a sheet-shaped solid electrolyte (LATP, LAGP, LLZP, LLZTO LGPS, LiSiPS, LiPS, LTP, similar to Argyrodite, lithium nitrides, lithium hydrides, perovskite, lithium halide, lithium phosphorus oxynitride, lithium thiophosphorus phosphate, etc.).

[0035] And the solid electrolyte sheet (10) hardened in the above sheet form can be prepared by cutting it into corresponding area units.

[0036] When a solid electrolyte sheet (10) with a thickness of several µm to several hundred µm is prepared by the above process, the next step is b), in which a battery base body (100) is prepared using the prepared solid electrolyte sheet (10).

[0037] At this time, a positive electrode layer (21), a negative electrode layer (22), and a current collector layer (30) can be laminated on the surface of the prepared solid electrolyte sheet (10) to prepare a battery base body (100).

[0038] Each of the above anode layer (21), cathode layer (22), and current collector layer (30) has a thickness of several µm to several hundred µm and can be prepared by cutting it into a sheet of a size corresponding to the area of ​​the solid electrolyte sheet (10).

[0039] Here, the anode layer (21) is made of any one of the following materials: LCO, LVP, LFP, NCM, Li compound, etc., and the cathode layer (22) is made of any one of the following materials: solid electrolyte + graphite, solid electrolyte + graphite + silicon, solid electrolyte + LVP, solid electrolyte + cathode material, and the current collector layer (30) may be provided as a metal (Al, Cu, Ag, Au, Ni, Pd, Mo, W, etc.) paste, a sheet-shaped thin plate, or a conductive film (metal substrate + conductive adhesive layer or metal substrate protective layer + metal substrate + conductive adhesive layer).

[0040] The anode layer (21), cathode layer (22), and current collector layer (30) prepared as described above form a battery base body (100) in which the anode layer (21) is laminated on one side of the solid electrolyte sheet (10) placed at the center and the cathode layer (22) is laminated on the other side of the solid electrolyte sheet (10).

[0041] In addition, a current collector layer (30) can be laminated on the respective surfaces of the positive electrode layer (21) and the negative electrode layer (22) to form a battery base body (100).

[0042] Then, when the stacking of the anode layer (21), cathode layer (22), and current collector layer (30) is completed based on the solid electrolyte sheet (10), the battery base body (100) is formed by integrating them using a uniaxial press or hydrostatic press (WIP, CIP, HIP) at a temperature of 25 to 70 degrees and a pressure of several kgf / ㎠ to several hundred kgf / ㎠.

[0043] Additionally, each of the anode layer (21), cathode layer (22), and current collector layer (30) can be laminated based on the solid electrolyte sheet (10).

[0044] At this time, a pattern of the corresponding shape is printed on one side of the solid electrolyte sheet (10) placed at the center using a liquid ink containing a substance forming an anode, and by drying the pattern printed on one side of the solid electrolyte sheet (10), an anode layer (21) with a thickness of several µm to several hundred µm can be formed on one side of the solid electrolyte sheet (10).

[0045] Then, a pattern of the corresponding shape is printed on the other side of the solid electrolyte sheet (10) using a liquid ink containing a material that forms a cathode, and by drying the pattern printed on the other side of the solid electrolyte sheet (10), a cathode layer (22) with a thickness of several µm to several hundred µm can be formed on the other side of the solid electrolyte sheet (10).

[0046] A pattern of the corresponding shape may be printed on the respective surfaces of the positive electrode layer (21) and the negative electrode layer (22) using liquid ink containing a material that forms a current collector, and by drying the pattern printed on the respective surfaces of the positive electrode layer (21) and the negative electrode layer (22), a current collector layer (30) may be formed on the respective surfaces of the positive electrode layer (21) and the negative electrode layer (22) to form a battery base body (100).

[0047] In addition, the present invention is described as being limited to having the solid electrolyte sheet (10) as a single layer, but is not limited thereto and may form a battery base body (100) with a structure in which a plurality of the solid electrolyte sheets (10) are stacked.

[0048] In this case, an anode layer (21) is laminated on one side of a current collector layer (30) positioned at the center, a cathode layer (22) is laminated on the other side of the current collector layer (30), and a solid electrolyte sheet (10) is laminated on each of the anode layer (21) and the cathode layer (22).

[0049] A current collector layer (30) is stacked together with a negative electrode layer (22) on the surface of a solid electrolyte sheet (10) stacked in one direction based on the above current collector layer (30), and a current collector layer (30) is stacked together with a positive electrode layer (21) on the surface of a solid electrolyte sheet (10) stacked in the other direction, thereby forming a battery base body (100) having a structure in which a solid electrolyte, a positive electrode, and a negative electrode are alternately stacked in series.

[0050] At this time, as the solid electrolyte sheets (10) are stacked in series, the voltage of the power output from the battery can be output at a voltage that is doubled.

[0051] When the battery base body (100) is prepared by the above process, the next step is c), in which the prepared battery base body (100) is fired.

[0052] At this time, the firing of the battery base body (100) is carried out inside a firing furnace (oven: H) that can maintain a high temperature of 600°C to 900°C for a corresponding period of time, and it is preferable that the atmosphere inside the firing furnace (H) be maintained as one of air, reducing, or inert atmosphere depending on the physical properties of the solid electrolyte.

[0053] And before firing the battery base body (100), a crushing groove (101) of a certain depth can be formed on the surface of the battery base body (100) using a cutting blade (not shown).

[0054] At this time, the crushing groove (101) may be formed in a specific pattern such as horizontal, vertical, or diagonal based on the plane of the battery base body (100), or in a shape without a specific pattern, and it is preferable that the longitudinal direction of the crushing groove (101) be formed parallel to the bending axis of the all-solid-state battery.

[0055] The crushing groove (101) formed on the surface of the battery base body (100) facilitates the crushing of the solid electrolyte sheet (10) embedded in the battery base body (100) in the future.

[0056] In addition, when the firing of the battery base body (100) is completed, a notch (102) of a certain depth can be formed on the surface of the battery base body (100) that has been fired by laser or mechanical processing (not shown).

[0057] At this time, the above notch (102) also allows for easy crushing of the solid electrolyte sheet (10) embedded in the battery base body (100) in the future.

[0058] The above notch (102) is formed in a direction perpendicular to the longitudinal direction of the battery base body (100), and the bending direction of the all-solid-state battery may be bent with the longitudinal direction of the crushing groove (101) as an axis, but is not limited thereto, and may be formed in a specific pattern such as horizontal, vertical, or diagonal with respect to the plane of the battery base body (100), or in a shape without a specific pattern, and it is preferable that the longitudinal direction of the above notch (102) be formed parallel to the bending axis of the all-solid-state battery.

[0059] The above-described crushing groove (101) and notch (102) processing may be performed optionally, and may be performed so that only one of the crushing groove (101) and notch (102) is formed, or may be performed so that both the crushing groove (101) before firing and the notch (102) after firing are formed, or may be performed by omitting the processing of the crushing groove (101) and notch (102) and performing the crushing processing.

[0060] When the firing of the battery base body (100) is completed by the above process, the next step is d), in which a conductive film (110) is bonded to one side and the other side of the battery base body (100) that has been fired, and the next step is e), in which the battery base body (100) is crushed.

[0061] At this time, the conductive film (110) is a film having a metal substrate component such as Al, Cu, Ni, Ag, Au, Pd, and a conductive adhesive component, and the bonding (laminating) is performed by a press or roll-to-roll method, and the conductive film (110) is bonded to one side and the other side of the battery base body (100).

[0062] Here, when the roll-to-roll method is implemented, the battery base body (100) is crushed by the pressure of the pressure roller (R). For example, crushing is performed in a direction perpendicular to the length of the battery base body (100), so that a crack having a length in a direction perpendicular to the length direction of the battery base body (100) is formed in the solid electrolyte sheet (10). (When the solid electrolyte sheet (10) is crushed, it may be crushed in a surface processing shape (by the crushing groove (101) and notch (102)) before / after firing, or crushed in a horizontal, vertical, diagonal, specific pattern, or any shape without a fixed shape.)

[0063] Since a conductive film (110) is placed on one side and the other side of the battery base body (100) during the crushing process, it is prevented that a part of the battery base body (100) is detached to the outside even when the battery base body (100) is crushed.

[0064] Accordingly, the battery base body (100) in which the solid electrolyte sheet (10) is crushed by the above-described process has flexibility so that it can be bent along the longitudinal direction of the crack.

[0065] In addition, after the bonding (laminating) of the conductive film (110) using a roll-to-roll method, a crushing process may be separately performed using a separate roll-to-roll pressure roller (R).

[0066] At this time, if the crushing process is performed using a separate roll-to-roll pressure roller (R), it is not performed along the entire length of the battery base body (100), but only the portion to be folded can be selectively crushed.

[0067] Here, the solid electrolyte sheet (10) in which the crushing process is completed is crushed into monocell units of a certain pattern by the crushing grooves (101) and notches (102) formed before and after firing, respectively, or the solid electrolyte sheet (10) that is crushed without surface processing before and after firing is crushed without having a specific shape.

[0068] And the solid electrolyte sheet (10) to which the conductive film (110) is bonded is attached to the conductive film (110) after crushing, so that it can maintain the shape of the all-solid-state battery after crushing and also impart flexibility to the all-solid-state battery.

[0069] When the process of bonding and crushing the conductive film (110) is completed through the above process, the next step is f), in which the battery base body (100) with the conductive film (110) bonded to its surface is folded into corresponding length units and stacked in length units.

[0070] Accordingly, by the method for manufacturing a flexible all-solid-state battery according to an embodiment of the present invention, a flexible battery manufactured by connecting a monocell unit or multiple monocell batteries can be folded into specific length units and stacked (laminated) in the vertical or horizontal direction to produce a battery having the area of ​​at least one monocell in a large area.

[0072] Referring to Fig. 3, first, in step a), a solid electrolyte sheet (10) is prepared.

[0073] At this time, the solid electrolyte sheet (10) is prepared by preparing an electrolyte raw material (oxide-based solid electrolyte) as a fine powder, mixing a binder and a solvent with the corresponding properties with the fine powder to form a slurry, and then processing the slurry through one of the casting processes of tape casting, slot die casting, and doctor braid casting to form a solid electrolyte sheet (10) with a thickness of several µm to several hundred µm.

[0074] Here, the slurry containing the electrolyte raw material is dried during casting, and as the moisture (solvent) contained in the slurry is removed, it hardens into a sheet-shaped solid electrolyte (LATP, LAGP, LLZP, LLZTO LGPS, LiSiPS, LiPS, LTP, similar to Argyrodite, lithium nitrides, lithium hydrides, perovskite, lithium halide, lithium phosphorus oxynitride, lithium thiophosphorus phosphate, etc.).

[0075] And the solid electrolyte sheet (10) hardened in the above sheet form can be prepared by cutting it into corresponding area units.

[0076] When a solid electrolyte sheet (10) with a thickness of several µm to several hundred µm is prepared by the above process, the next step is b), in which a battery base body (100) is prepared using the prepared solid electrolyte sheet (10).

[0077] At this time, a positive electrode layer (21) and a negative electrode layer (22) are laminated on the surface of the prepared solid electrolyte sheet (10) to prepare a battery base body (100).

[0078] Each of the above anode layer (21) and cathode layer (22) has a thickness of several µm to several hundred µm and can be prepared by cutting it into a sheet of a size corresponding to the area of ​​the solid electrolyte sheet (10).

[0079] Here, the anode layer (21) is made of any one of the following materials: LCO, LVP, LFP, NCM, Li compound, etc., and the cathode layer (22) is made of any one of the following materials: solid electrolyte + graphite, solid electrolyte + graphite + silicon, solid electrolyte + LVP, solid electrolyte + cathode material.

[0080] The anode layer (21) and cathode layer (22) prepared as described above are formed such that the anode layer (21) is laminated on one side of the solid electrolyte sheet (10) placed at the center, and the cathode layer (22) is laminated on the other side of the solid electrolyte sheet (10) to form a battery base body (100).

[0081] Then, when the stacking of the anode layer (21) and the cathode layer (22) is completed based on the solid electrolyte sheet (10), they are integrated by uniaxial press or hydrostatic press (WIP, CIP, HIP) at a temperature of 25 to 70 degrees and a pressure of several kgf / ㎠ to several hundred kgf / ㎠ to form a battery base body (100).

[0082] Additionally, a pattern of the corresponding shape can be printed on one side of the solid electrolyte sheet (10) that is placed in the center using a liquid ink containing a substance that forms an anode, and by drying the pattern printed on one side of the solid electrolyte sheet (10), an anode layer (21) with a thickness of several µm to several hundred µm can be formed on one side of the solid electrolyte sheet (10).

[0083] Then, a pattern of the corresponding shape is printed on the other side of the solid electrolyte sheet (10) using a liquid ink containing a material that forms a cathode, and by drying the pattern printed on the other side of the solid electrolyte sheet (10), a cathode layer (22) with a thickness of several µm to several hundred µm can be formed on the other side of the solid electrolyte sheet (10).

[0084] When the battery base body (100) is prepared by the above process, the next step is c), in which the prepared battery base body (100) is fired.

[0085] At this time, the firing of the battery base body (100) is carried out inside a firing furnace (oven: H) that can maintain a high temperature of 600°C to 900°C for a corresponding period of time, and it is preferable that the atmosphere inside the firing furnace (H) be maintained as one of air, reducing, or inert atmosphere depending on the physical properties of the solid electrolyte.

[0086] And before firing the battery base body (100), a crushing groove (101) of a certain depth can be formed on the surface of the battery base body (100) using a cutting blade (not shown).

[0087] At this time, the crushing groove (101) may be formed in a specific pattern such as horizontal, vertical, or diagonal based on the plane of the battery base body (100), or in a shape without a specific pattern, and it is preferable that the longitudinal direction of the crushing groove (101) be formed parallel to the bending axis of the all-solid-state battery.

[0088] The crushing groove (101) formed on the surface of the battery base body (100) facilitates the crushing of the solid electrolyte sheet (10) embedded in the battery base body (100) in the future.

[0089] In addition, when the firing of the battery base body (100) is completed, a notch (102) of a certain depth can be formed on the surface of the battery base body (100) that has been fired by laser or mechanical processing (not shown).

[0090] At this time, the above notch (102) also allows for easy crushing of the solid electrolyte sheet (10) embedded in the battery base body (100) in the future.

[0091] The above notch (102) is formed in a direction perpendicular to the longitudinal direction of the battery base body (100), and the bending direction of the all-solid-state battery may be bent with the longitudinal direction of the crushing groove (101) as an axis, but is not limited thereto, and may be formed in a specific pattern such as horizontal, vertical, or diagonal with respect to the plane of the battery base body (100), or in a shape without a specific pattern, and it is preferable that the longitudinal direction of the above notch (102) be formed parallel to the bending axis of the all-solid-state battery.

[0092] The above-described crushing groove (101) and notch (102) processing may be performed optionally, and may be performed so that only one of the crushing groove (101) and notch (102) is formed, or may be performed so that both the crushing groove (101) before firing and the notch (102) after firing are formed, or may be performed by omitting the processing of the crushing groove (101) and notch (102) and performing the crushing processing.

[0093] When the firing of the battery base body (100) is completed by the above process, the next step is d), in which a conductive film (110) is bonded to one side and the other side of the battery base body (100) that has been fired, and the next step is e), in which the battery base body (100) is crushed.

[0094] At this time, the conductive film (110) is a film having a metal substrate component such as Al, Cu, Ni, Ag, Au, Pd, and a conductive adhesive component, and the bonding (laminating) is performed by a press or roll-to-roll method, and the conductive film (110) is bonded to one side and the other side of the battery base body (100).

[0095] Here, when the roll-to-roll method is implemented, the battery base body (100) is crushed by the pressure of the pressure roller (R). For example, crushing is performed in a direction perpendicular to the length of the battery base body (100), so that a crack having a length in a direction perpendicular to the length direction of the battery base body (100) is formed in the solid electrolyte sheet (10). (When the solid electrolyte sheet (10) is crushed, it may be crushed in a surface processing shape (by the crushing groove (101) and notch (102)) before / after firing, or crushed in a horizontal, vertical, diagonal, specific pattern, or any shape without a fixed shape.)

[0096] Since a conductive film (110) is placed on one side and the other side of the battery base body (100) during the crushing process, it is prevented that a part of the battery base body (100) is detached to the outside even when the battery base body (100) is crushed.

[0097] Accordingly, the battery base body (100) in which the solid electrolyte sheet (10) is crushed by the above-described process has flexibility so that it can be bent along the longitudinal direction of the crack.

[0098] In addition, after the bonding (laminating) of the conductive film (110) using a roll-to-roll method, a crushing process may be separately performed using a separate roll-to-roll pressure roller (R).

[0099] At this time, if the crushing process is performed using a separate roll-to-roll pressure roller (R), it is not performed along the entire length of the battery base body (100), but only the portion to be folded can be selectively crushed.

[0100] Here, the solid electrolyte sheet (10) in which the crushing process is completed is crushed into monocell units of a certain pattern by the crushing grooves (101) and notches (102) formed before and after firing, respectively, or the solid electrolyte sheet (10) that is crushed without surface processing before and after firing is crushed without having a specific shape.

[0101] And the solid electrolyte sheet (10) to which the conductive film (110) is bonded is attached to the conductive film (110) after crushing, so that it can maintain the shape of the all-solid-state battery after crushing and also impart flexibility to the all-solid-state battery.

[0102] When the process of bonding and crushing the conductive film (110) is completed through the above process, the next step is f), in which the battery base body (100) with the conductive film (110) bonded to its surface is folded into corresponding length units and stacked in length units.

[0103] Accordingly, by the method for manufacturing a flexible all-solid-state battery according to an embodiment of the present invention, a flexible battery manufactured by connecting a monocell unit or multiple monocell batteries can be folded into specific length units and stacked (laminated) in the vertical or horizontal direction to produce a battery having the area of ​​at least one monocell in a large area.

[0104] The present invention has been described with reference to embodiments illustrated in the drawings, but this is merely illustrative, and those skilled in the art will understand that various modifications and equivalent alternative embodiments are possible therefrom. Accordingly, the true technical scope of protection of the present invention should be determined by the technical spirit of the appended claims. Explanation of the symbols

[0106] 10: Solid electrolyte sheet 21: Anode layer 22: Cathode layer 30: Entire house floor 100: Battery base body 101: Crushing groove 102: Notch 110: Conductive film H: Kiln R: Pressure roller

Claims

Claim 1 a) a step of preparing a solid electrolyte sheet; b) a step of preparing a battery base body using the prepared solid electrolyte sheet; c) a step of calcining the prepared battery base body; d) a step of bonding a conductive film to one side and the other side of the battery base body after calcination is completed; e) a step of crushing the battery base body; and f) a step of folding a battery base body having a conductive film bonded to its surface, wherein the step of c) firing the prepared battery base body further includes a process of forming a notch of a certain depth on the surface of the battery base body after firing is completed by laser processing, and the step of e) crushing the battery base body is carried out together with the step of d) bonding a conductive film to one side and the other side of the battery base body after firing is completed, wherein a pressure roller bonding the conductive film to one side and the other side of the battery base body presses the notch formed on the surface of the battery base body to form a crack having a length in the longitudinal direction of the notch formed on the surface of the battery base body, thereby causing the battery to be crushed. Claim 2 A method for manufacturing a flexible all-solid-state battery according to claim 1, wherein the battery base body comprises a solid electrolyte sheet, a positive electrode layer laminated on one side of the solid electrolyte sheet, a negative electrode layer laminated on the other side of the solid electrolyte sheet, and a current collector layer laminated on the respective surfaces of the positive electrode layer and the negative electrode layer. Claim 3 A method for manufacturing a flexible all-solid-state battery according to claim 1, wherein the battery base body comprises the solid electrolyte sheet, a positive electrode layer laminated on one side of the solid electrolyte sheet, and a negative electrode layer laminated on the other side of the solid electrolyte sheet. Claim 4 A method for manufacturing a flexible all-solid-state battery according to claim 1, characterized in that, when the battery base body is prepared, a process of forming a crushing groove of a certain depth on the surface of the battery base body with a cutting blade is included. Claim 5 A method for manufacturing a flexible all-solid-state battery according to claim 4, characterized in that the longitudinal direction of the crushing groove is formed parallel to the bending axis of the all-solid-state battery. Claim 6 delete Claim 7 A method for manufacturing a flexible all-solid-state battery according to claim 1, characterized in that the longitudinal direction of the notch is formed parallel to the bending axis of the all-solid-state battery. Claim 8 A method for manufacturing a flexible all-solid-state battery according to claim 1, characterized in that when the crushed battery base body is bent, it is bent along an axis in a direction perpendicular to the longitudinal direction of the conductive film.

Citation Information

Patent Citations

  • Flexible all-solid-state battery and preparation method thereof

    CN107611340A

  • Solid electrolyte sheet for all solid battery and method for manufacturing the same, and all solid battery using the same

    KR1020180076954A

  • Method for manufacturing of All-Solid Battery

    KR1020230108472A

  • Composite solid electrolyte for secondary battery, secondary battery including the same, and preparing method thereof

    KR1020220069620A

  • Sheet for folding batteries, folding battery and method for producing folding battery

    WO2023276283A1